Managing Cross-Cultural Communication / Principles and Practice - Maude Barry (Palgrave Macmillan, 2011)
This book is an engaging introduction to the principles and practice of global cross-cultural communication. Principles, What is Culture. Cultural Values in Business and Society, Language Matters, Nonverbal Aspects of Cross-Cultural Communication, Prejudice and Stereotypes, Practice, Expatriate Performance, Cross-Cultural Adjustment, Developing Cross-Cultural Skills, Communicating Across Cultural Distance, Managing and Working in Multicultural Teams, Cross-Cultural Meeting and Negotiations, Cross-Cultural Interviews and Selection, Power of Social Networks.